2021
DOI: 10.1016/j.nutos.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and determinants of deficiency among Palestinian females of childbearing age: A case control study

Abstract: Some statistically significant correlations were reported and discussed between different parameters. Conclusions: Vitamin D deficiency is prevailing health threating condition among Palestinian females of childbearing age, justifying the necessity for national vitamin D supplementation strategy to ameliorate such prevalent health condition. The current intervention has successfully restorer the deficient status and replenish the body of subjects with sufficient vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In pregnancy, the calcium demand of the fetus results in profound changes in maternal calcium homeostasis, whereas parathyroid plays a major role in calcium and bone metabolism in the non-pregnant state, vitamin D appears to be a prominent regulator during pregnancy [ 8 ]. Several studies have shown that vitamin D deficiency and thyroid function can lead to a series of adverse health disorders during pregnancy, including gestational hypertension, cardiovascular disease, metabolic health, diabetes, multiple sclerosis, bone strength and cancers [ 9 , 10 ]. This study was designed to explore the relationship between vitamin D and thyroid and parathyroid hormone levels in Palestinian pregnant females during the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, the calcium demand of the fetus results in profound changes in maternal calcium homeostasis, whereas parathyroid plays a major role in calcium and bone metabolism in the non-pregnant state, vitamin D appears to be a prominent regulator during pregnancy [ 8 ]. Several studies have shown that vitamin D deficiency and thyroid function can lead to a series of adverse health disorders during pregnancy, including gestational hypertension, cardiovascular disease, metabolic health, diabetes, multiple sclerosis, bone strength and cancers [ 9 , 10 ]. This study was designed to explore the relationship between vitamin D and thyroid and parathyroid hormone levels in Palestinian pregnant females during the first trimester of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin D deficiency is associated with adverse clinical outcomes like gingival inflammation and impaired bone growth. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, vitamin D deficiency has been considered a global health problem affecting approximately 50% of the worldwide population. 7 It exacerbates many illnesses, such as diabetes mellitus, cardiovascular diseases, autoimmune diseases, osteoporosis, and cancer. In addition, vitamin D deficiency is associated with adverse clinical outcomes like gingival inflammation and impaired bone growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation